2021
DOI: 10.5005/jp-journals-10071-23764
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Left Ventricular Outflow Tract and Carotid Artery Velocity Time Integral as Predictors of Fluid Responsiveness in Patients with Sepsis and Septic Shock

Abstract: A bstract Background: Transthoracic echocardiography is a reliable method to measure a dynamic change in left ventricular outflow tract velocity time integral (LVOTVTI) and stroke volume (SV) in response to passive leg raising (PLR) and can predict fluid responsiveness in critically ill patients. Measuring carotid artery velocity time integral (CAVTI) is easier, does not depend on adequate cardiac window, and requires less skill and expertise than LVOTVTI. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The majority were unspecified/heterogeneous [ 9 , 25 , 29 , 32 , 34 , 35 , 37 , 39 ] or septic shock [ 26 , 30 , 31 , 33 , 36 , 40 ], with a minority of studies having cohorts of patients with haemorrhagic shock [ 27 ] or cardiogenic shock [ 38 ]. A fluid challenge was administered either by crystalloid bolus [ 27 31 , 34 , 37 , 40 ], passive leg raise (PLR) [ 25 , 26 , 32 , 38 , 39 ], or a combination of the two [ 9 , 33 , 35 , 36 ]. Crystalloid volume was determined by weight (6-7 ml/kg) or a predetermined value (200 ml–500 ml).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority were unspecified/heterogeneous [ 9 , 25 , 29 , 32 , 34 , 35 , 37 , 39 ] or septic shock [ 26 , 30 , 31 , 33 , 36 , 40 ], with a minority of studies having cohorts of patients with haemorrhagic shock [ 27 ] or cardiogenic shock [ 38 ]. A fluid challenge was administered either by crystalloid bolus [ 27 31 , 34 , 37 , 40 ], passive leg raise (PLR) [ 25 , 26 , 32 , 38 , 39 ], or a combination of the two [ 9 , 33 , 35 , 36 ]. Crystalloid volume was determined by weight (6-7 ml/kg) or a predetermined value (200 ml–500 ml).…”
Section: Resultsmentioning
confidence: 99%
“…Crystalloid volume was determined by weight (6-7 ml/kg) or a predetermined value (200 ml–500 ml). The reference standards most commonly used were left ventricular outflow tract (LVOT) velocity time integral (VTI) [ 26 , 27 , 31 , 33 , 34 , 37 , 38 ] and noninvasive cardiac output monitor (NICOM) (Cheetah Medical, Inc) [ 9 , 25 , 28 , 29 ], with some studies used pulmonary artery catheter (PAC) [ 32 , 36 , 40 ], pulse contour cardiac output (PiCCO) (PULSION Medical Systems AG, Munich, Germany) [ 30 , 35 ], and FloTrac (Edwards Lifesciences, Irvine, CA, USA) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were conducted on ICU patients in either septic, cardiogenic or undifferentiated shock, and reported a median AUROC of 0.88 (IQR: 0.76-0.99), a sensitivity of 83% (IQR: 72%-94%), and a specificity of 86% (IQR:78%-94%). However, one study that compared septic shock patients with healthy controls found that AUROC predicting FR was lowest in the shock cohort (Chowhan et al 2021).…”
Section: Haemodynamically Unstable Patientsmentioning
confidence: 99%
“…Chowhan et al compared the efficacy of left ventricular outflow tract velocity time integral (LVOTVTI) and carotid artery velocity time integral (CAVTI) as predictors of fluid responsiveness in patients with sepsis and septic shock. 6 Patients were divided into three groups— sepsis, septic shock, and controls. Since there were three groups, comparisons of numerical variables were done using analysis of variance (for normally distributed data) or Kruskal–Wallis test (for skewed data).…”
Section: T Ests For C Omparisonmentioning
confidence: 99%
“…These represented paired readings from the same individual and comparison of prereading and postreading was performed using the paired t -test. 6 Verma et al evaluated the role of physiotherapy on oxygen requirements and physiological parameters in patients with COVID-19. 7 Each patient had pretreatment and post-treatment data for heart rate and oxygen supplementation recorded on day 1 and day 14.…”
Section: T Ests For C Omparisonmentioning
confidence: 99%